Evaluation of small-diameter silk vascular grafts implanted in dogsCentral MessagePerspective - Takashi Tanaka, DVM, PhD; Ryo Tanaka, DVM, PhD; Yoko Ogawa, BS; Yoshihide Takagi, BS; Masataka Sata, MD, PhD; Tetsuo Asakura, PhD (JTCVS Open, 2021)
Objectives: Vascular replacement is one treatment for cardiovascular disease. However, in blood vessels with a diameter less than 6 mm, the existing artificial vascular grafts may be occluded by thrombus formation or intimal hyperplasia. Thus, new artificial vascular grafts need to be developed. We have developed a small-diameter artificial vascular graft made of silk fibroin. The implantation of such graft has been evaluated mainly in rats. However, only a few reports describe long-term implantation in large animal models. Therefore, modified silk fibroin artificial vascular grafts were implanted in the femoral arteries of dogs, and their patency and remodeling ability were investigated. Methods: Six beagles weighing 10 to 12 kg were used for the in vivo study. Grafts (4 cm length × 3.5 mm inner diameter) were implanted in the femoral artery of 6 dogs. The patency of the graft was monitored using vascular ultrasound apparatus. At 3 months', 5 months', and 1-year postimplantation, the graft was retrieved and conducted histopathologic examination. Results: No side effects, such as ischemia, paralysis, and edema of the hind legs, were observed postimplantation. Five of the 6 grafts exhibited a high patency rate, and the lumen was covered with vascular endothelial cells in the central part of the graft 3 months’ postimplantation. Conclusions: Based on these results, artificial silk fibroin vascular grafts implanted in the femoral arteries of dogs exhibit high patency and remodeling ability. Silk fibroin grafts may be clinically applicable as an artificial vascular graft in small-diameter <6 mm.